2017
DOI: 10.1371/journal.pone.0181481
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of AMP-activated protein kinase on the epithelial-mesenchymal transition in retinal pigment epithelial cells

Abstract: The epithelial-mesenchymal transition (EMT) in retinal pigment epithelial (RPE) cells plays a central role in the development of proliferative vitreoretinopathy (PVR). The purpose of this study was to investigate the effect of AMP-activated protein kinase (AMPK), a key regulator of energy homeostasis, on the EMT in RPE cells. In this study, EMT-associated formation of cellular aggregates was induced by co-stimulation of cultured ARPE-19 cells with tumor necrosis factor (TNF)-α (10 ng/ml) and transforming growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 37 publications
1
32
1
Order By: Relevance
“…In mice tumor kidney tissues, demonstrated reduced cell proliferation, more apoptotic cells, and significantly reduced expression of HIF‐2α, VEGF, and p‐Akt. Recent studies have shown that AICAR suppresses the epithelial–mesenchymal transition and the formation of aggregates by retinal pigment epithelial cells and that it upregulates IL‐6, VEGF, and MMP‐2 and ‐9, partially through AMPK activation . We demonstrated that in H460 cells, MAPK signal pathway activation is crucial in the NiCl 2 ‐induced expression of VEGF (Figure ).…”
Section: Resultssupporting
confidence: 51%
“…In mice tumor kidney tissues, demonstrated reduced cell proliferation, more apoptotic cells, and significantly reduced expression of HIF‐2α, VEGF, and p‐Akt. Recent studies have shown that AICAR suppresses the epithelial–mesenchymal transition and the formation of aggregates by retinal pigment epithelial cells and that it upregulates IL‐6, VEGF, and MMP‐2 and ‐9, partially through AMPK activation . We demonstrated that in H460 cells, MAPK signal pathway activation is crucial in the NiCl 2 ‐induced expression of VEGF (Figure ).…”
Section: Resultssupporting
confidence: 51%
“…The activated SMADs combine with SMAD4 to form a SMAD complex, which then enters the nucleus and combines with regulatory elements to regulate the expression of key genes associated with EMT. In addition to SMAD-dependent signaling, TGF β induces EMT through SMAD independent signaling pathways including Rho GTPase-dependent pathways ( Lee, Ko & Joo, 2008 ), PI3K/Akt pathway ( Huang et al, 2017 ; Yokoyama et al, 2012 ), mitogen-activated kinase (MAPK) pathways ( Chen et al, 2017 ; Lee et al, 2020 ; Matoba et al, 2017 ; Schiff et al, 2019 ) and Jagged/Notch signaling pathway ( Zhang et al, 2017 ). The MAPK signaling pathways include extracellular signal-regulated kinase(ERK) MAPK pathway, p38 MAPK pathway, and JUN N-terminal kinase (JNK) pathway ( Parrales et al, 2013 ; Schiff et al, 2019 ; Xiao et al, 2014 ; Zhang et al, 2018a ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…How this broad reprogramming of membrane traffic by AMPK contributes to some of the established cell and tissue outcomes of AMPK is an important area of investigation with many open questions. For example, many studies have revealed that AMPK regulates epithelial‐mesenchymal transition (EMT), a cellular differentiation program that is important for development and tissue repair and that is also critical to progression of diseases such as cancer and kidney disease . Importantly, EMT elicits and requires broad remodeling of membrane traffic .…”
Section: Control Of Endocytic Membrane Traffic By Ampkmentioning
confidence: 99%